The Usage of Monte Carlo Simulation to Predict The Sales of Sustainable Batik Products in Small Medium Enterprise - Manik Ayu; Surjo Hadi; Muhammad Rizky Nafiuddin (Tibuana, 2023)
As an intangible cultural heritage, Indonesian Batik continues to develop and is increasingly in demand by domestic and foreign people. In the current era, the concept of making batik that is sustainable or more environmentally friendly has emerged, one of the efforts is in terms of coloring that uses natural dyes. This innovation produces softer batik colors aka soil colors, besides that the manufacturing process is longer than using chemical dyes, so the price is more expensive. With these changes, analyzing the development of sustainable batik sales is important to identify an increase in sales. This study aims to determine the prediction of sustainable batik sales with Monte Carlo simulations precisely and accurately. The data processed is batik production using natural dyes, then converted into probability distributions in the form of compulsive frequencies and then generated random numbers to obtain random numbers. After that, group the interval limit of the random number that has been obtained and continue with the simulation process so that it gets the simulation results and the percentage of accuracy using the Monte Carlo method. The results of the study on data processing from 2020 to 2021 have an accuracy of 90%. So this research is very appropriate for predicting sales for the next year.